Application of Composite Fittings in Construction Future - Turopov M; Akromov X; Komilov X; A.A.Bekov; N.R.Ametov; B.B.Kushbakova; Y.M.Yusufjonov; A.X.Umarov; Q.A.Rustamov (International Journal on Orange Technologies, 2021)
This article presents the advantages and disadvantages of using composite reinforcement in construction in comparison with traditional steel reinforcement